Vapor‐Phase Hydrothermal Growth of Novel Segmentally Configured Nanotubular Crystal Structure. Issue 18 (16th April 2013) - Liu, Porun; Zhang, Haimin; Liu, Hongwei; Wang, Yun; An, Taicheng; Cai, Weiping; Yang, Huagui; Yao, Xiangdong; Zhu, Guangshan; Webb, Robyn; Zhao, Huijun
<x xml:space="preserve">Abstract</x> A new form of nanotubular crystal structure is directly grown by a vapor‐phase hydrothermal method via an epitaxial orientated crystal growth mechanism. The as‐prepared nanotubes possess a unique multi‐tunnel core‐shell layered nanotubular structure with droplet shaped polygonal periphery and segmental crystal configuration. They are dimension‐tunable and demonstrate superior ion exchange properties in terms of exchange rate and ion accommodating capacity. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>